2019
DOI: 10.1186/s13012-019-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

Using a RE-AIM framework to identify promising practices in National Diabetes Prevention Program implementation

Abstract: Background The National Diabetes Prevention Program (National DPP) is rapidly expanding in an effort to help those at high risk of type 2 diabetes prevent or delay the disease. In 2012, the Centers for Disease Control and Prevention funded six national organizations to scale and sustain multistate delivery of the National DPP lifestyle change intervention (LCI). This study aims to describe reach, adoption, and maintenance during the 4-year funding period and to assess associations between site-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…Furthermore, programs and coaches might target their early retention efforts on participants who are struggling to find early successes. Several additional retention strategies have been proposed in the literature, including health care provider referrals (29), nonmonetary incentives (29), partner enrollment (30), and recruiting participants who are ready to change behavior (11). In addition, Venditti et al (31) found that many participant barriers can be successfully addressed through behavioral problem-solving approaches that lifestyle change coaches can be trained to use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, programs and coaches might target their early retention efforts on participants who are struggling to find early successes. Several additional retention strategies have been proposed in the literature, including health care provider referrals (29), nonmonetary incentives (29), partner enrollment (30), and recruiting participants who are ready to change behavior (11). In addition, Venditti et al (31) found that many participant barriers can be successfully addressed through behavioral problem-solving approaches that lifestyle change coaches can be trained to use.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation science frameworks have rarely been applied in the eld of lipidology or FH (22). However, their use and bene t have been demonstrated in the implementation of other chronic disease programs such as diabetes control (23). Using frameworks such as RE-AIM will help lipidologists, and others implementing MDLCs, understand the full impact of their programs and where the barriers and facilitators to access or care exist (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CDC launched a program from 2012 to 2016 that funded 6 national organizations to scale and sustain the DPP across the nation and evaluated via the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. [27][28][29] The program was designed to facilitate broad adoption, implementation, and sustainment. These organizations conducted programs in 164 sites in 38 states and reached almost 15,000 participants.…”
Section: Diabetes Prevention Programmentioning
confidence: 99%